Driver’s Drowsiness and Alcoholic Intoxication Detection with Image Processing: https://doi.org/10.46610/JOEDE.2020.v06i02.005 - Sharma, Sumit (Journal of Electronic Design Engineering, 2020)
This paper covers a real-time approach regarding driver drowsiness and alcoholic intoxication. We come across a large number of accidents in our day to day life because of alcoholic intoxication and driver drowsiness. With the help of an embedded system using Microcontrollers, we can reduce the number of accidents. For this, in this paper, a model is proposed using Raspberry-Pi, Arduino U.N.O, Web Camera, Open CV, and Numpy Libraries to control this issue. In this model, an open-source Web camera connected with Raspberry Pi having a Raspbian Operating System installed with a facility of python IDLE, Open CV, and Numpy installed in it. The Raspberry Pi microcontroller serially interfaced with Arduino U.N.O. The Raspberry Pi coding is in python and it deals with vision sensing during driver drowsiness and Arduino is taking care of sensing the breath of the driver and issuing a command to the relay to alarm the buzzer and turning off the ignition to stop the car.